Detached Islands: Artificial Islands as adaptation challenges in the making - Portman, Michelle Eva (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
There is surprisingly little information and concern within academic literature in the field of coastal or marine planning and management related to the issue of artificial islands. This is particularly noteworthy considering the climate change phenomenon, vis-à-vis sea-level rise, the urgent need for adaptation, efforts aiming for sustainable use of coastal areas, and the recent focus in academic circles on marine spatial planning. Most literature (including grey literature) on artificial islands appears in the engineering and geology disciplines and is focused on energy extraction, i.e., oil and gas. Yet some coastal nations are intent on solving problems of lack of space and other resource shortages through construc- tion of near-shore artificial islands for myriad uses, including commercial, residential and transportation infrastructure. This paper presents a limited review of the policy literature about planning and construction of artificial islands. It reflects what repercussions artificial islands portend for marine conservation, sustainability and, most importantly, how climate change adaptation is highlighted or neglected in spatial solutions addressed by the building of nearshore artificial islands. The Israeli situation, where tenders have been recently published calling for planning and building of islands in the Mediterranean Sea, serves as an example.